Isolated cranio-orbitofacial neurofibroma mimicking vascular malformation. (2nd January 2018) - Chahal, Harinder S.; Kuiper, Brandon; Braich, Puneet S.; Glover, A. Tyrone
ABSTRACT: Isolated neurofibromas in the absence of systemic neurofibromatosis are known as solitary or localized neurofibromas. When present in the orbit, these lesions may appear clinically and radiographically similar to other tumors, complicating diagnosis and management. Key radiographic signs may guide clinicians to the correct diagnosis when the presentation and patient demographic data obfuscate the disease entity. We present a case of a large multi-lobulated neurofibroma misdiagnosed as a lymphangioma. A brief review of these tumors emphasizing key radiographic features is also included.